Pengaruh Teams Games Tournament Berbantuan Kartu Aksara Jawa Terhadap Keterampilan Menulis Aksara Jawa - Yolinda Mardhika Putri; Abduh, Muhammad (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Language is the ability possessed by humans to communicate with other human beings. In Indonesia, particularly in the Central Java Region, Javanese language learning is implemented as part of the local curriculum. Javanese language learning includes Javanese script as one of its components, which requires the mastery of Javanese script character to form sentences. This research aims to determine the influence of cooperative learning using the teams games tournament model with the assistance of Javanese script cards on the Javanese script writing skills of fifth-grade students at SDN 3 Ngeblak. This study is categorized as quantitative reasearch using a pre-experimental method with a one group pre-test post-test design. The population in this study consists of fifth grade students at SDN 3 Ngeblak. Data collection techniques involve tests, including pre-test and post test. Data analysis techniques include two types: instrument validation and data analysis test. Instrument validation involves validity and reliability, while data analysis test include normality tests and hypothesis tests. Based on the calculations from the pre-test and post-test, the average pre-test score was 50.24, while the average post-test score was 87.88 with a significance value of 0.00, which is less than 0.05. Based on the results obtained, it can be concluded that the use of Javanese script cards with the cooperative learning model, specifically the teams games tournament, has an impact on the Javanese script writing skills of fifth-grade students. The use of these Javanese script cards is expected to provide an engaging learning experience for students and encourage their active participation in the learning process.